The organization of flash electroretinography unit in Veterinary Medicine - Honsho, Cristiane Dos Santos [UNESP]; Oriá, Arianne Pontes [UNESP]; Lazaro Júnior, Luiz Paulo Da Veiga Monteiro; Dorea Neto, Francisco [UNESP]; Laus, José Luiz [UNESP] (Universidade Federal de Santa Maria, 2004)
Electroretinography is the technique that allows the evaluation of changes in electrical potential that occur when the eye is stimulated by light. Such changes reflect the response of several retinal cells including photoreceptors (cones and rods). Thus it evaluates the retinal functionality and can diagnose abnormalities in retinas seem to be normal by ophthalmoscopy. Due to the constant evolution in veterinary ophthalmology, new centers of retinal electrophysiology have been introduced around the world either for early diagnosis of retinopathies or for preoperative evaluation of animals with cataracts and glaucoma, as well as for continuing research. The Ophthalmology Unit of the Governador Laudo Natel Veterinary Teaching Hospital, in the Faculty of Agronomic and Veterinary Sciences (FCAV) - Sao Paulo State University (UNESP) - Jaboticabal Campus, Brazil, supported by the Fundação de Amparo à Pesquisa do Estado de São Paulo - FAPESP (Sao Paulo State Foundation for Research), set up the Unit of Ocular Electrophysiology for animals in order to provide conditions for the diagnosis of retinopathies. As a pioneering venture in Brazil, the organization of the services faced many challenges till the moment it was set up: the organization and arrangement of appropriate rooms, independent electrical distribution for the installation of separate pieces of equipment, adaptation of containment tables, training and qualification of the staff, and the elaboration and standardization of anesthetic and stimulation protocols. The wealth of information generated by our experience gave us the inspiration to write this paper, which aims to contribute to the work of researchers and veterinary ophthalmologists in this new and opportune field of specialization.

Eletrorretinografia é a técnica que possibilita observar mudanças no potencial elétrico, que ocorrem quando o olho é estimulado pela luz. Tais mudanças refletem a resposta de várias células retinianas, incluindo os fotorreceptores (cones e bastonetes). Com ela, portanto, é possível avaliar a funcionalidade da retina e diagnosticar alterações, mesmo em retinas normais à oftalmoscopia. Em face do crescente desenvolvimento da oftalmologia, no âmbito da Veterinária, novos centros de eletrofisiologia da retina vêm sendo implementados em todo o mundo, tanto para o diagnóstico precoce de retinopatias, como para avaliação pré-operatória de animais com catarata e glaucoma ou, ainda, direcionados à pesquisa. A Unidade de Oftalmologia do Hospital Veterinário Governador Laudo Natel, da Faculdade de Ciências Agrárias e Veterinárias (FCAV) - Universidade Estadual Paulista (UNESP) - Campus de Jaboticabal, com o apoio da Fundação de Amparo à Pesquisa do Estado de São Paulo - FAPESP, visando a implementar condições diagnósticas em retinopatias, implantou a Unidade de Eletrofisiologia da Retina para animais. Por ser empreendimento pioneiro, no Brasil, sua organização passou por inúmeras intercorrências até que fosse consignado. Entre elas, a organização e montagem de salas apropriadas, distribuição elétrica independente para a instalação de equipamentos, visando a diminuir interferências externas, adequação de mesas de contenção, treinamento e habilitação de pessoal, elaboração e padronização de protocolos anestésicos e de estimulação, entre outras. A riqueza de informações e as experiência geradas obstinam a conceber este trabalho que visa a contribuir com pesquisadores e oftalmologistas veterinários neste, recente e oportuno, campo de especialização.
Organização de uma unidade de eletrorretinografia flash em Medicina Veterinária
Keywords: electroretinography; retina; electrophysiology; dogs; eletrorretinografia; retina; eletrofisiologia; cães